2017
DOI: 10.1186/s13065-017-0356-3
|View full text |Cite
|
Sign up to set email alerts
|

Development of new analytical methods for the determination of caffeine content in aqueous solution of green coffee beans

Abstract: BackgroundThis study was conducted to develop fast and cost effective methods for the determination of caffeine in green coffee beans. In the present work direct determination of caffeine in aqueous solution of green coffee bean was performed using FT-IR-ATR and fluorescence spectrophotometry. Caffeine was also directly determined in dimethylformamide solution using NIR spectroscopy with univariate calibration technique.ResultsThe percentage of caffeine for the same sample of green coffee beans was determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
24
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 23 publications
3
24
0
1
Order By: Relevance
“…This indicated that the caffeine content of green coffee beans obtained from the plants growing at different altitudes of geographical location is significantly different. In support to this study different value of caffeine contents in green coffee beans have been reported by the previous researchers [6,8,[24][25][26][27]. For example, an average value of 1.10% (w/w) by HPLC methods for 42 Ethiopian coffee samples [6], and in the range 0.96−1.23% (w/w) for Arabic green coffee beans [27] were reported for their caffeine contents.…”
Section: Determination Of Caffeine Content Of Green Coffee Beans By Usupporting
confidence: 85%
See 2 more Smart Citations
“…This indicated that the caffeine content of green coffee beans obtained from the plants growing at different altitudes of geographical location is significantly different. In support to this study different value of caffeine contents in green coffee beans have been reported by the previous researchers [6,8,[24][25][26][27]. For example, an average value of 1.10% (w/w) by HPLC methods for 42 Ethiopian coffee samples [6], and in the range 0.96−1.23% (w/w) for Arabic green coffee beans [27] were reported for their caffeine contents.…”
Section: Determination Of Caffeine Content Of Green Coffee Beans By Usupporting
confidence: 85%
“…In summary, all the coffee samples have the caffeine level in the range of the caffeine contents of different Arabica coffee reported previously [6,8,[24][25][26][27]]. The variation in caffeine level of green coffee beans samples may be due to geographical origins which might have different altitude, soil type, rain fall and other agricultural as well as environmental conditions.…”
Section: Determination Of Caffeine Content Of Green Coffee Beans By Umentioning
confidence: 66%
See 1 more Smart Citation
“…NIR spectroscopy is characterized by speed, reliability, simplicity, security, low operation cost, minimum sample processing, low instrumental maintenance, allowing various analyses simultaneously and not requiring the use of chemicals. 8,17,18 This technique has already proven useful for the prediction of several properties in coffee samples and has been applied in the determination of antioxidants, 19,20 caffeine, [21][22][23] cafestol and kahweol, 24 roasting degree prediction, 25 chemical composition of defective beans, 11 sensory characteristics 18,26,27 and geographical origin. 28 In this context, the objective of the work presented here was to evaluate the potential of NIR spectroscopy and spectral pre-processing methods associated with partial least squares regression (PLS-R) in determining the pH and acidity of green coffee samples.…”
Section: Introductionmentioning
confidence: 99%
“…Caffeine levels from Garut, Pangalengan, and Tasikmalaya were 1.454 ± 0.004%, 1.574 ± 0.082%, and 2.280 ± 0.004%.Caffeine (1,3,7-trimethylxanthine) is a central nervous system stimulant that prevents drowsiness, improves short-term memory, influences human circadian timing, and improves the effectiveness of particular drugs. It is an alkaloid which naturally found in the seeds, leaves or fruits of more than 63 plants species worldwide [1][2][3]. Caffeine is widely consumed by humans for many years as foods and beverages containing caffeine including coffee beverage [4][5][6].…”
mentioning
confidence: 99%